Influence of Marine Yeast Debaryomyces hansenii on Antifungal and Physicochemical Properties of Chitosan-Based Films - César A. García-Bramasco; Francisco J. Blancas-Benitez; Beatriz Montaño-Leyva; Laura M. Medrano-Castellón; Porfirio Gutierrez-Martinez; Ramsés R. González-Estrada (Journal of Fungi, 2022)
Chitosan-based film with and without antagonistic yeast was prepared and its effect against Penicillium italicum was evaluated. The biocompatibility of yeast cells in the developed films was assessed in terms of population dynamics. Furthermore, the impact on physicochemical properties of the prepared films with and without yeast cells incorporated were evaluated in terms of thickness, mechanical properties, color and opacity. Chitosan films with the antagonistic yeast entrapped exhibited strong antifungal activity by inhibiting the mycelial development (55%), germination (45%) and reducing the sporulation process (87%). Chitosan matrix at 0.5% and 1.0% was maintained over 9 days of cell viability. However, at 1.5% of chitosan the population dynamics was strongly affected. The addition of yeast cells only impacted color values such as a*, b*, chroma and hue angle when 1.0% of chitosan concentration was used. Conversely, luminosity was not affected in the presence of yeast cells as well as the opacity. Besides, the addition of antagonistic yeast improved the mechanical resistance of the films. The addition of D. hansenii in chitosan films improve their efficacy for controlling P. italicum, and besides showed desirable characteristics for future use as packaging for citrus products.